2018
DOI: 10.1186/s12936-018-2609-6
|View full text |Cite|
|
Sign up to set email alerts
|

Malaria causes long-term effects on markers of iron status in children: a critical assessment of existing clinical and epidemiological tools

Abstract: BackgroundMost epidemiological studies on the interplay between iron deficiency and malaria risk classify individuals as iron-deficient or iron-replete based on inflammation-dependent iron markers and adjustment for inflammation by using C-reactive protein (CRP) or α-1-acid glycoprotein (AGP). The validity of this approach and the usefulness of fibroblast growth factor 23 (FGF23) as a proposed inflammation-independent iron marker were tested.MethodsConventional iron markers and FGF23 were measured in children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 46 publications
3
15
0
Order By: Relevance
“…Although serum ferritin was also measured, we did not use this biomarker for defining iron status in this study because of the clear absence of correlation of this biomarker and anaemia in our study population. This finding was in accordance with findings from other teams showing that serum ferritin is less accurate in assessing ID in Malawian children even after adjustment for inflammation as malaria infection may lead to long lasting ferritin elevation [42, 100]. The second limitation is the absence of screening for malaria and any inherited disorders known to influence the markers of iron status or the biological regulation of iron homeostasis [16, 101103].…”
Section: Discussionsupporting
confidence: 86%
“…Although serum ferritin was also measured, we did not use this biomarker for defining iron status in this study because of the clear absence of correlation of this biomarker and anaemia in our study population. This finding was in accordance with findings from other teams showing that serum ferritin is less accurate in assessing ID in Malawian children even after adjustment for inflammation as malaria infection may lead to long lasting ferritin elevation [42, 100]. The second limitation is the absence of screening for malaria and any inherited disorders known to influence the markers of iron status or the biological regulation of iron homeostasis [16, 101103].…”
Section: Discussionsupporting
confidence: 86%
“…Samples from children (aged 1-12) were collected from Hohoe, Ghana, an area of high P . falciparum malaria transmission intensity, from May – August 2015, as described previously [ 47 , 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…Study participants were enrolled on admission at Hohoe municipal hospital (Febrile children) or from within the Hohoe and Asutsauare communities after engagement with community/opinion leaders. This was followed by a durbar in the community to explain the study in the local language to the residents [ 48 ]. Subjects were recruited after informed written consent had been obtained; in the case of children, from a parent or legal guardian.…”
Section: Methodsmentioning
confidence: 99%
“…Another method, the BRINDA regression correction (RC) approach, developed by the BRINDA project, does not rely on the CRP cut-off ≤5 mg/L (Namaste et al 2017). Nonetheless, Castberg et al (2018) have shown that in a malaria endemic setting the respective values of CRP and AGP came down to below the ≤5mg/L and ≤1g/L (i.e., healthy concentrations) two weeks earlier than that of ferritin which remained elevated at a substantial level. This suggests that the RC method, based on an assumption of linear regression between CRP/AGP and ferritin, may not be sufficient to fully compensate for the effect of malaria/inflammation on ferritin.…”
Section: Introductionmentioning
confidence: 95%